MR1 recycling and blockade of endosomal trafficking reveal distinguishable antigen presentation pathways between Mycobacterium tuberculosis infection and exogenously delivered antigens - Karamooz, Elham (Sci Rep, 2019)
The MHC-Ib molecule MR1 presents microbial metabolites to MR1-restricted T cells (MR1Ts). Given the ubiquitous expression of MR1 and the high prevalence of human MR1Ts, it is important to understand the mechanisms of MR1-dependent antigen presentation. Here, we show that MR1-dependent antigen presentation can be distinguished between intracellular Mycobacterium tuberculosis (Mtb) infection and exogenously added antigens. Although both Mtb infection and exogenously added antigens are presented by preformed MR1, only exogenously added antigens are capable of reusing MR1 that had been bound to the folic acid metabolite 6-formylpterin (6-FP). In addition, we identify an endosomal trafficking protein, Syntaxin 4, which is specifically involved in the presentation of exogenously delivered antigens but not Mtb-dependent antigen presentation. These data reveal there are multiple ways that MR1 can sample antigens and that MR1-mediated sampling of intracellular Mtb infection is distinguishable from the sampling of exogenously added antigens.